Resonances in QCD - Lutz, Matthias F. M.; Lange, Jens Sören; Pennington, Michael; Bettoni, Diego; Brambilla, Nora; Crede, Volker; Eidelman, Simon; Gillitzer, Albrecht; Gradl, Wolfgang; Lang, Christian B.; Metag, Volker; Nakano, Takashi; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2016)
We report on the EMMI Rapid Reaction Task Force meeting ‘Resonances in QCD’, which took place at GSI October 12-14, 2015. A group of 26 people met to discuss the physics of resonances in QCD. The aim of the meeting was defined by the following three key questions:•What is needed to understand the physics of resonances in QCD?•Where does QCD lead us to expect resonances with exotic quantum numbers?•What experimental efforts are required to arrive at a coherent picture? For light mesons and baryons only those with up, down and strange quark content were considered. For heavy-light and heavy-heavy meson systems, those with charm quarks were the focus. This document summarizes the discussions by the participants, which in turn led to the coherent conclusions we present here.